2020
DOI: 10.3390/medicina56040174
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Neonatal/Maternal Morbidity and Mortality in African American Women with Placental Abruption

Abstract: Background and Objectives: Risk factors for neonatal/maternal morbidity and mortality in placental abruption have been incompletely studied in the current literature. Most of the research overlooked the African American population as mostly Caucasian populations are selected. We aimed to find which risk factor influence the neonatal and maternal outcome in cases of placental abruption occurring in African American pregnant women in an inner-city urban setting. Materials and Methods: We performed a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(46 reference statements)
0
13
1
Order By: Relevance
“…When abruptio placenta occurs, the neonatal mortality is reported to be approx. 30% [ 8 ], and the prognosis may depend on the severity of abruptio placenta rather than DDI.…”
Section: Discussionmentioning
confidence: 99%
“…When abruptio placenta occurs, the neonatal mortality is reported to be approx. 30% [ 8 ], and the prognosis may depend on the severity of abruptio placenta rather than DDI.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of nicotine's vasoactive properties and carbon monoxide's chronic hypoxia, cigarette smoking during pregnancy may be associated with placenta previa risk: chronic hypoxia in comparison to non-smokers, smokers have a larger placenta and a greater chance of placental attachment to the cervical os. [32] As a result of maternal cocaine use, sympathetic blood vessels in the uterus are under perfused, consequently, a larger placenta is formed that encroaches on the cervical os, leading to premature delivery [20]. There is a higher risk of placenta previa in women who have chronic or underlying high blood pressure.…”
Section: Figure-ii: a Partial Or Minor Placenta Previamentioning
confidence: 99%
“…Another study identified several risk factors that contribute to negative maternal outcomes among African American women, including trauma during delivery by c-section (Elkafrawi et al, 2020). According to the National Center for Health Statistics, Black women were slightly more likely to undergo a Cesarean Section (C-section) than other racial groups, with 35.5% of live births from African American women being C-section compared to 31% for white women, 32.5% for Asian and Pacific Islander women, and 28.9% for Native American women (2021).…”
Section: Literature Reviewmentioning
confidence: 99%